2021
DOI: 10.3390/nano11112803
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Synthesis of Multi-Element Nanoparticles

Abstract: The advantages of gas-phase synthesis of nanoparticles in terms of size control and flexibility in choice of materials is well known. There is increasing interest in synthesizing multi-element nanoparticles in order to optimize their performance in specific applications, and here, the flexibility of material choice is a key advantage. Mixtures of almost any solid materials can be manufactured and in the case of core–shell particles, there is independent control over core size and shell thickness. This review p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 150 publications
3
9
0
Order By: Relevance
“…[58] Paradoxically, there is an enhanced ability to access certain compositions from the lower likelihood of being mass-transfer limited in the overall process compared to the liquid-phase. [59,60] More rapid growth rates also tend to introduce a greater degree of defects, which can be beneficial for certain applications (e. g., catalysts, membranes). [61] A final drying step is furthermore obviated with the gas-phase approach, including the use of supercritical fluids.…”
Section: Focus Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] Paradoxically, there is an enhanced ability to access certain compositions from the lower likelihood of being mass-transfer limited in the overall process compared to the liquid-phase. [59,60] More rapid growth rates also tend to introduce a greater degree of defects, which can be beneficial for certain applications (e. g., catalysts, membranes). [61] A final drying step is furthermore obviated with the gas-phase approach, including the use of supercritical fluids.…”
Section: Focus Of the Reviewmentioning
confidence: 99%
“…Such thermodynamically more stable species inherently possess simpler chemistry, and thereby limit the compositional possibilities [58] . Paradoxically, there is an enhanced ability to access certain compositions from the lower likelihood of being mass‐transfer limited in the overall process compared to the liquid‐phase [59,60] . More rapid growth rates also tend to introduce a greater degree of defects, which can be beneficial for certain applications (e. g., catalysts, membranes) [61] .…”
Section: Introductionmentioning
confidence: 99%
“…To manifest its coming-of-age, a subject-based textbook was published in 2017, with contributions by some of the pioneers and main current key players in the field. 5 Two recent reviews on the subject, one by an author of the current perspective 6 and one by the group at Castilla la Mancha 7 focused on the growth of multi-elemental nanoparticles from a computational and an experimental viewpoint, respectively. Another two reviews by the Swansea group 8 and Teer Coatings, 9 on the other hand, focused on the technique's potential for catalysis and sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Therefore, attempts have been made to accelerate the activity and product selectivity of well-known iron based catalysts, resulting in important outcomes, including iron based binary alloy nanoparticles, supported Fe monolayers, Fe nanoclusters (Fe-NC), and core-shell structure of a-Fe@Fe 2 O 3 nanorods. 7,[18][19][20][21][22] Suryanto et al experimentally demonstrated that the NRR activity was profoundly increased on a-Fe nanorods, resulting from enhancing the surface area and increasing the N 2 solubility. 7 An alloyed catalyst comprising Fe and Ni was studied by Renner et al for the electrochemical NRR, and it was reported that the catalyst had an optimum activity with a high faradaic efficiency (FE).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a smaller size dodecahedral NC with fewer atoms can provide a well-defined (110) facet compared to the reported octahedral structure. 18 Therefore, it is reasonable to model a dodecahedral Fe 65 NC in terms of computational costs and catalytic activity. Furthermore, core–shell nanoparticles are widely recognized as potential catalysts for various catalytic applications with high efficiency.…”
Section: Introductionmentioning
confidence: 99%